0198 The chlorinated hydrocarbons contaminated groundwater and the reproductive hazard. (21st August 2017) - Lin, Ching-Chun; Chen, Pau-Chung; Tsai, Meng-Shan; Chen, Yu Chan; Ren, Yu Ling
Abstract : Our study was to investigate the association between the birth outcome and infant mortality among the community with chlorinated organic contaminated groundwater. The parents who lived in the area around the factory from1978 to1997were recruited. According to the groundwater hydrogeology, we classified into three areas, factory located as a high-exposure area, the downstream as low-exposure areas, and upstream as reference areas. Analysis with the multiple logistic regression and adjusted for infant sex, parity, maternal marital status, maternal age at birth, maternal education, and maternal occupation, the adjusted odds ratio for preterm delivery among the high-exposure and low-exposure areas. We exclude the population who ever worked in the factory. Associations between the exposure area and adverse birth outcomes were divided into four periods 1978–82, 1983–87, 1988–92, and 1993–97. For the preterm delivery, the odds ratio for the factory located were1.60 (CI=1.14–2.24) for the period of 1993–1997, 1.67 (CI=1.03–2.71) for the period of 1988–1992 and 1.57 (95% CI=1.07–2.30) for the downstream for the period of 1988–1992. For the low birth weight, the odds ratio for the downstream were1.36 (CI=1.00–1.84) for the period of 1993–1997. The infant mortality have the trend for the The Chlorinated Hydrocarbons organic solvents contaminated water and the environment could be increased the risk of preterm delivery and the low birth weight. The more evidence need more explore and further studies need to strength the relation.